A new dithiolopyrrolone antibiotic triggered by a long fermentation of Saccharothrix algeriensis NRRL B‐24137 in sorbic acid‐amended medium. (11th September 2019) - Merrouche, R.; Yekkour, A.; Coppel, Y.; Bouras, N.; Zitouni, A.; Lebrihi, A.; Mathieu, F.; Sabaou, N.
Abstract: Saccharothrix algeriensis NRRL B‐24137 is an actinobacterium isolated from Algerian Saharan soil. It produces bioactive compounds belonging to the dithiolopyrrolone class of antibiotics, which are characterized by the possession of a unique pyrrolinonodithiole nucleus. Dithiolopyrrolones are known for their strong antibacterial and antifungal activities. This class of antibiotics generated great interest after the discovery of their anticancer properties. In this study, an antibiotic named PR11, produced after a long bacterial fermentation (11 days) in sorbic acid‐containing culture broth, was characterized as a new dithiolopyrrolone derivative. After HPLC analysis and purification, the chemical structure of this antibiotic was determined by 1 H‐ and 13 C‐nuclear magnetic resonance, mass and UV‐visible data. PR11 was thus characterized as an iso‐hexanoyl‐pyrrothine, a novel dithiolopyrrolone derivative. The minimum inhibitory concentrations of the new induced antibiotic were determined against several pathogenic micro‐organisms. A moderate to strong activity was noted against all Gram‐positive bacteria, filamentous fungi and yeasts tested. Significance and Impact of the Study: Given the strong activities of dithiolopyrrolones against diverse prokaryotic and eukaryotic micro‐organisms including potent selective‐anticancer activity, the discovery of new‐related derivatives draw continuous attention for therapeutic research. Depending on nature and concentration of added precursor, Saccharothrix algeriensis NRRL B‐24137 produce several dithiolopyrrolone coumpounds. In this study, sorbic acid addition combined to long fermentation duration was shown to induce the biosynthesis of a novel dithiolopyrrolone derivative. After purification and full spectroscopic and spectrometric study, the compound was characterized as iso‐hexanoyl‐pyrrothine. In the future investigation for novel dithiolopyrrolone discovery, fermentation duration should be regarded as a key parameter as well. Abstract : Significance and Impact of the Study: Given the strong activities of dithiolopyrrolones against diverse prokaryotic and eukaryotic micro‐organisms including potent selective‐anticancer activity, the discovery of new‐related derivatives draw continuous attention for therapeutic research. Depending on nature and concentration of added precursor, Saccharothrix algeriensis NRRL B‐24137 produce several dithiolopyrrolone coumpounds. In this study, sorbic acid addition combined to long fermentation duration was shown to induce the biosynthesis of a novel dithiolopyrrolone derivative. After purification and full spectroscopic and spectrometric study, the compound was characterized as iso‐hexanoyl‐pyrrothine. In the future investigation for novel dithiolopyrrolone discovery, fermentation duration should be regarded as a key parameter as well.